Pelatihan Penggunaan Cairan Klorin Untuk Menurunkan Angka Mikroorganisme Pada Kaset Radiografi - Kurniawati, Ary; Handoko, Bagus Dwi; Kurniawan, Andrey Nino (Politeknik Negeri Cilacap, 2024)
Radiography has an important role in diagnosing a patient's disease, but the equipment used has a considerable risk as a place for the development of nosocomial bacteria which can endanger the patient and radiographer. Cassettes, one of the tools in radiography, have the potential to become a medium for disease transmission and based on previous research it has been proven that there are microorganisms and fungi on the cassettes, so the cassettes need to be cleaned regularly. One of the duties of a radiographer in the field of radiology services is the management of radiology equipment facilities and infrastructure. Cleaning the cassette with 70% alcohol can reduce the number of microorganisms on its surface. The methods in this activity are lectures, simulations, and practice cleaning cassettes with chlorine. The activities were carried out at the Laboratory of the Department of Radiodiagnosis and Radiotherapy Technique at the Semarang Health Polytechnic Ministry with radiographers from hospitals and clinical laboratories in the city of Semarang. The activity begins with the registration, opening, delivering material to the participants, and the simulation of resource persons. Evaluation is done by filling in the pretest and posttest. The evaluation results showed an increase in participants' knowledge of 63% about how to clean cassettes using liquid chlorine to reduce the number of microorganisms on radiographic cassettes. With this training, radiographers are expected to be able to apply cleaning radiographic cassettes with liquid chlorine 0,5% in their respective institutions.